Hermeneutics from Exegesis to Aesthetics: Towards Establishing Key Principles for Literary Hermeneutics - Mahmoud Moawad Hemida Sokar (Maǧallaẗ Kulliyyaẗ Al-ādāb Ǧāmiʿaẗ Būrsaʿīd, 2019)
Reading the literary text is a two-way interactive process between the reader and the text. This process occurs through a triangular interaction between three factors: the reader, the text, and the cultural atmosphere of this text. In this interaction, the reader’s role is not negative but it is very active and vital, as he ⁄she has to work on making up the text’s meaning. Thus, the text’s interpretation is not solid process; it changes according to certain criteria. Like the Alexandrite gemstone, whose color varies according to the surrounded circumstances, the text is always open to many possible interpretations.